COVID-19's Impact on Black, Female Correctional Officers and Justice-Involved Individuals at Rikers Island Jail. (July 2022) - Martin-Howard, Simone
Through in-depth interviews, this study focuses on the experiences and perceptions of 15 Black, female correctional officers (COs) employed at Rikers Island, one of the country's biggest jail complexes. Furthermore, this paper underlines the experiences of COs during the COVID-19 pandemic, which hit New York City particularly hard in spring 2020. Thematic analysis suggests that participants do not receive needed mental health services from the Department of Correction; experience physical and mental health stressors as a result of the COVID-19 pandemic; and negatively perceive the impact of COVID-19 on the physical and mental health of justice-involved individuals.